Twenty-four hour plasma levels of growth hormone and prolactin in Huntington's disease. Issue 12 (December 1983) - Durso, R; Tamminga, C A; Ruggeri, S; Denaro, A; Kuo, S; Chase, T N
Abstract : Since hypothalamic neural degeneration is thought to occur in individuals with Huntington's disease, anterior pituitary hormone secretion which is in part regulated by the hypothalamus, was postulated to be altered in patients with this disease. To test this proposal, nine females with Huntington's disease were matched with controls to participate in a 24-hour basal level study of growth hormone and prolactin concentration in plasma. Patients who were free from all centrally active medication for at least six months and normal volunteers had blood sampled at 30-minute intervals over 24 hours in a minimal stress environment. The results demonstrated that plasma levels of growth hormone were elevated throughout the 24-hour time period in Huntington's disease individuals. Despite the elevation, the mean growth hormone curve of the Huntington's disease group retained characteristics similar to the control curve throughout the 24-hour time. Basal 24-hour plasma prolactin concentrations in Huntington's disease patients showed no difference from those in control individuals.